Aladdin (2019) [videorecording (DVD)] - Ritchie, Guy; Smith, Will, 1968-; Massoud, Mena; Scott, Naomi, 1993-; Kenzari, Marwan, 1983- (Buena Vista Home Entertainment, 2019)
A street rat frees a genie from a lamp, granting all of his wishes and transforming himself into a charming prince to marry a beautiful princess. But soon, an evil sorcerer becomes fixated on securing the lamp for his own sinister purposes.